2001
DOI: 10.2135/cropsci2001.4141054x
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Retention Capacities of Irrigated Soft White Spring Wheat Flours

Abstract: The solvent retention capacity (SRC) test uses the ability of flour to retain a range of solvents as a means of evaluating multiple aspects of wheat (Triticum aestivum L.) quality: pentosan content, starch damage, gluten strength, and general water retention. To assess the utility of the SRC in cultivar evaluation, 26 soft white spring wheat genotypes were produced in seven irrigated environments, and milling and baking quality parameters for these genotypes were determined. Solvent (water, 500 g kg−1 sucrose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
177
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(214 citation statements)
references
References 8 publications
29
177
3
5
Order By: Relevance
“…The results were in concordance with several authors who reported negative correlations between AWRC and spread ratio (Leon et al 1996;Kissel and Lorenz 1976;Abboud et al 1985). Guttieri et al (2001) found that cookie diameter and top grain score is negatively correlated with sodium carbonate, sucrose, and lactic SRC.…”
Section: Quality Parameters Of Cookiesmentioning
confidence: 92%
See 1 more Smart Citation
“…The results were in concordance with several authors who reported negative correlations between AWRC and spread ratio (Leon et al 1996;Kissel and Lorenz 1976;Abboud et al 1985). Guttieri et al (2001) found that cookie diameter and top grain score is negatively correlated with sodium carbonate, sucrose, and lactic SRC.…”
Section: Quality Parameters Of Cookiesmentioning
confidence: 92%
“…Millers are of the opinion that granulation is very important in the production of quality flour. It has been suggested that flour particle size, damaged starch and protein quality and quantity have effects on the baked products (Guttieri et al 2001). Hard wheat is more difficult to reduce to flour-sized particles.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the influence of storage protein alleles on quality traits determined that HMW glutenin alleles encoded at Glu-A1 and Glu-B1 cause significant differences in quality parameters related to gluten strength (extensibility and strength), flour yield, and FP while HMW glutenin subunits Glumx2 + Glumy12, Glumx3 + Glumy12, and Glumx4 + Glumy12, Glumx2 + Glumy12 at the Glu-m1 locus, have no effect on extensibility, strength, flour yield, FP, and mixograph parameters (Igrejas et al, 2002). In our study gluten strength functionality measured by LA was independent to the other SRC tests, yet these traits have been reported to be positively associated (Guttieri et al, 2001). The lack of correlation observed in our study was probably because LA is a specific test for the glutenin network swelling behavior (Kweon et al, 2011).…”
Section: Wheat Quality Laboratory (Swql) Of the United States Departmmentioning
confidence: 40%
“…However, in a study of three soft wheat populations, just one population showed a positive correlation (0.47) between these traits (Guttieri & Souza, 2003). Lack of association of these two traits was also observed in a study of soft white wheat (Guttieri et al, 2001). This association of LA and FP has been explained by the effect of HMW glutenin subunits, which are part of the total FP.…”
Section: Wheat Quality Laboratory (Swql) Of the United States Departmmentioning
confidence: 86%
See 1 more Smart Citation